Seen and heard: combining in-depth interviewing with social messaging to study the lived experiences of gifted youth in high power distance cultures - Wan Mohd Nor, Sofiya; Krauss, Steven; Roslan, Samsilah; Syed-Abdullah, Sharifah Intan Sharina (SAGE Publications Inc., 2024)
Qualitative research with gifted youth presents unique challenges because of their tendency to display qualities such as perfectionism, overexcitability, and asynchronous development. Studying gifted youth in cultural contexts marked by high power distance between young people and adults can further compound these challenges by limiting gifted youths’ feelings of psychological safety during data collection. As a result, gifted youth often withhold information or give perceived culturally appropriate answers to adult researchers’ queries. Drawing on a larger phenomenological study of the formation of self-concept among eight Malaysian gifted youth aged between 18 and 25 years old, this article describes how an innovative application of combining semi-structured interviews with WhatsApp social messaging diaries helped minimize the power imbalance between the researcher and youth participants. The paper describes the unique methodological strategy of combining in-depth phenomenological interviews with WhatsApp diary entries to collect data from a hard-to-reach population. Specific techniques employed included using a conversational interview style, self-disclosing personal information to build trust, and validating participants’ feelings and experiences are discussed. Open-ended WhatsApp diary prompts and an extended time provided a sense of anonymity which allowed participants to recall their past and discuss sensitive experiences. Combining these techniques facilitated in-depth exploration into the lived experiences and challenges of being gifted, and how giftedness shaped participants’ self-concept. This is the first known study to document the use of social messaging applications as an effective journaling method for creating a familiar and safe space for special needs groups in high power distance cultures to share their experiences and feelings.